Three-loop ladder diagrams with two off-shell legs - Ming-Ming Long (Journal of High Energy Physics)
Abstract We present an analytic calculation of three-loop four-point Feynman integrals with two off-shell legs of equal mass. We provide solutions to the canonical differential equations of two integral families in both Euclidean and physical regions. They are validated numerically against independent computations. A total of 170 master integrals are expressed in terms of multiple polylogarithms up to weight six. Most of them are computed for the first time. Our results are essential ingredients of the scattering amplitudes for equal-mass diboson production at next-to-next-to-next-to-leading-order QCD at the LHC.